Discuss and Analyze the Role and Impact of Industrial Policy on Economic Development and especially in Developing Countries: (Between Opponents and Supporters) - saleh shafeek, Maryam (Al-Adab Journal, 2021)
Different countries, especially developing ones, have resorted since the middle of the last century to using industrial policy in order to expand the industrial base and push forward the economic development wheel. Tangible results have been achieved in many Asian countries, while no such results have been achieved in the countries of Latin America and Africa. Support has been dropped for the application of industrial policy since the mid-eighties of the last century because of the negative consequences resulting from it and then return again in the recent period. The research aims to analyze and discuss industrial policy and the extent of the need to use it in developing countries, it focuses on discussing the ideas and propositions of the two different approaches towards industrial policy. The first represents the position of those opposed to the industrial policy, and the second represents the position of those who support it. Those opposed to the industrial policy are the neoliberals in the United States of America who stress the role of the market in achieving development and point to the negative effects of industrial policy, while in favor of industrial policy book theoreticians Many economists because of the existence of globalization and the WTO rules and the changing nature of the global economy and that creates difficulties and impediments to developing countries and weaken the influence of industrial policy. Through analysis and discussion of the various propositions and evidence, the research ends with recommending the use of a carefully formulated industrial policy as a means to achieve economic development in developing countries and overcome the negative effects on them. With the call to adjust the policies and rules of the World Trade Organization and the global economic system in line with the need of developing countries for the development of industrialization and promoting economic development.